Low-frequency deep brain stimulation reveals resonant beta-band evoked oscillations in the pallidum of Parkinson’s Disease patients - Zapata Amaya, Valentina; Aman, Joshua E.; Johnson, Luke A.; Wang, Jing; Patriat, Remi; Hill, Meghan E.; MacKinnon, Colum D.; Cooper, Scott E.; Darrow, David; McGovern, Robert; Harel, Noam; Molnar, Gregory F.; et al. (Frontiers in Human Neuroscience, 2023)
Evidence suggests that spontaneous beta band (11-35Hz) oscillations in the basal ganglia thalamocortical (BGTC) circuit are linked to Parkinson’s disease (PD) pathophysiology. Previous studies on neural responses in the motor cortex evoked by electrical stimulation in the subthalamic nucleus have suggested that circuit resonance may underlie the generation of spontaneous and stimulation-evoked beta oscillations in PD. Whether these stimulation-evoked, resonant oscillations are present across PD patients in the internal segment of the globus pallidus (GPi), a primary output nucleus in the BGTC circuit, is yet to be determined. We characterized spontaneous and stimulation-evoked local field potentials (LFPs) in the GPi of four PD patients (five hemispheres) using deep brain stimulation (DBS) leads externalized after DBS implantation surgery. Our analyses show that low-frequency (2-4Hz) stimulation in the GPi evoked long-latency (>50ms) beta-band neural responses in the GPi in 4/5 hemispheres. We demonstrated that neural sources generating both stimulation-evoked and spontaneous beta oscillations were correlated in their frequency content and spatial localization. Our results support the hypothesis that the same neuronal population and resonance phenomenon in the BGTC circuit generates both spontaneous and evoked pallidal beta oscillations. These data also support the development of closed-loop control systems that modulate the GPi spontaneous oscillations across PD patients using beta band stimulation-evoked responses.